+0  
 
0
61
1
avatar

-3-2(2x-1)=-3(2x-5)-10

Guest Dec 11, 2017
Sort: 

1+0 Answers

 #1
avatar+81023 
+2

-3-2(2x-1)=-3(2x-5)-10     simplify

 

-3 - 4x + 2  = -6x + 15 - 10

 

-4x -  1  =  -6x + 5        add 1, 6x to both sides

 

2x  =  6           divide both sides by 2

 

x  =  6 / 2  =   

 

 

 

cool cool cool

CPhill  Dec 11, 2017

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details